Entrepreneurship Capital and Economic Performance - David B. Audretsch; Max Keilbach (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2002)
The neoclassical model of the production function, as applied by Robert Solow to build the neoclassical model of growth, linked labor and capital to output. More recently, Romer and others have expanded the model to include measures of knowledge capital. In this paper we introduce a new factor, entrepreneurship capital, and link it to output in the context of a production function model. This paper explains what is meant by entrepre-neurship capital and why it should influence economic output. A production function model including several different measures of entrepreneurship capital is then estimated for German regions. The results indicate that entrepreneurship capital is a significant and important factor shaping output and productivity. These results sug-gest a new direction for policy that focuses on instruments to enhance entrepreneurship capital.
Keywords: M13; O32; O47; 330; Production Function; Entrepreneurship Capital; Regional Economic Performance; Produktionsfunktion; Produktionsfaktor; Unternehmer; Unternehmensgründung; Schätzung; Deutschland